A Review of the Jordanian Framework Governing Foreign Workers - Aya, Al Dabbas (Essays of Faculty of Law University of Pécs, Yearbook of [year], 2025)
As Jordan continues to experience an increasing influx of foreign workers in the country due to political issues arising in neighbouring countries and Jordan’s strategic position, it was deemed necessary to provide a review of the current framework governing foreign workers and to demonstrate any issues in the current legislation. In this article, the authorused the descriptive analysis approach to provide a summary of the labor migration status in Jordan,The International framework that Jordan adheres to, the national laws and regulations in place to regulate foreign workforce, in addition to providing a critical analysis of the Kafala system in Jordan and reflecting on the issues it raises. The author concluded that Jordan’s current laws prohibit foreign workers from forming trade unions, or take leadership positions in any trade unions, contradicting the international guarantees provided by human rights conventions, additionally the author has shed a light on the consequences of implementing the Kafala (sponsorship) system.